Semantic interoperability for an autonomic knowledge delivery service - KEENEY, JOHN; LEWIS, DAVID; O'SULLIVAN, DECLAN; POWER, RUAIDHRI SEAN (Springer, 2005)
The development and deployment of interconnected networks is being increasingly limited by their complexity and the concomitant cost of managing the operational network. Autonomic Communication aims to reduce this cost, by migrating management intelligence towards the network elements and empowering operational support staff to specify what network behaviour in terms of goals and constraints. Towards this aim we propose a key infrastructural service that enables the efficient delivery of network operations knowledge to, and only to, nodes that have expressed an interest in that knowledge. This Knowledge Delivery Service mediates operational network knowledge in an open, ontological form, thereby promoting the graceful evolution of network management applications from contemporary to fully autonomic. To cope with the inevitable heterogeneity of knowledge across the population of network nodes, the service provides a level of semantic interoperability that will be transparent to the nodes providing and consuming knowledge. The Service will be based on content-based networking principles. This paper describes work towards supporting semantic interoperability in such a Knowledge Delivery Service.
PUBLISHED
Keywords: Computer Science